Determination of the enzymatic activity of α-amylase, glucoamylase, cellulase, pullulanase, and pectinase using the street-close and dinitrosalicylic acid (DNS) methods (Agroindustria, Sociedad y Ambiente, 2025)
Enzymes are proteins responsible for triggering, modifying, stopping, accelerating, or slowing down certain chemical reactions, specifically those that are thermodynamically possible. In other words, they are the substances responsible for regulating the functioning of living organisms. Enzymatic activity can be affected by various factors, such as temperature, pH, and concentration. Enzymes function best within specific temperature and pH ranges, and under suboptimal conditions, an enzyme can lose its ability to bind to a substrate. The main objective of this research was to evaluate the enzymatic activity of a group of commercial enzymes belonging to the experimental laboratory of the Biotechnology Division of the CIEPE Foundation. These include α-amylases, glucoamylases, pectinase, pullulanase, and cellulase. The activity of each of these enzymes was evaluated using the Street Close and Dinitrosalicylic acid (DNS) methods. The latter allows glucose production to be quantified by spectrophotometry over time as a measure of enzymatic activity for each of the enzymes evaluated. These methods demonstrated that each enzyme exhibited optimal enzymatic activity for use in various exploratory activities.
Keywords: Enzyme, Enzymatic Activity, Biotechnology.